The BiTE (bispecific T-cell engager) platform: Development and future potential of a targeted immuno-oncology therapy across tumor types - Einsele, Hermann; Borghaei, Hossein; Orlowski, Robert Z.; Subklewe, Marion; Roboz, Gail J.; Zugmaier, Gerhard; Kufer, Peter; Iskander, Karim; Kantarjian, Hagop M. (Cancer, 2020)
Immuno-oncology therapies engage the immune system to treat cancer. BiTE (bispecific T-cell engager) technology is a targeted immuno-oncology platform that connects patients' own T cells to malignant cells. The modular nature of BiTE technology facilitates the generation of molecules against tumor-specific antigens, allowing off-the-shelf immuno-oncotherapy. Blinatumomab was the first approved canonical BiTE molecule and targets CD19 surface antigens on B cells, making blinatumomab largely independent of genetic alterations or intracellular escape mechanisms. Additional BiTE molecules in development target other hematologic malignancies (eg, multiple myeloma, acute myeloid leukemia, and B-cell non-Hodgkin lymphoma) and solid tumors (eg, prostate cancer, glioblastoma, gastric cancer, and small-cell lung cancer). BiTE molecules with an extended half-life relative to the canonical BiTE molecules are also being developed. Advances in immuno-oncology made with BiTE technology could substantially improve the treatment of hematologic and solid tumors and offer enhanced activity in combination with other treatments.
CRIS-Team Scopus Importer:2023-03-23
Keywords: B cell; blinatumomab; hematologic malignancies; T cell; tumor-specific antigen